Hydrogeological conditions in the southern part of Dang valley, mid-western Nepal - Sapkota, Birendra (Himalayan Journal of Sciences, 2006)
The Dang valley consists of several patches of confined and unconfined aquifer systems. Drilling data reveals that the northern portion of the study area has more permeable surfaces than the southern and central portions. Annual domestic draft and safe yield were calculated to be 7.43 x106 m3/year and 3.16 x 107 m3/year, respectively. The fact that the safe yield is higher than the annual draft indicates the presence of good groundwater potential in the study area.Key words: terrace, lithology, aquifer, tubewell, yield, draft, piezometric surface, water tableHimalayan Journal of Sciences 1(2): 119-122, 2003